The effect of 25 m versus 50 m course length on backstroke performance - An analysis of national and international swimmers - Janoschka, A.; Wolfrum, W.; Knechtle, B.; Rüst, C. A.; Rosemann, T.; Lepers, R. (Journal of Athletic Enhancement, 2014)
Background: The aims of the present study were (i) to examine effects of course length (25 m versus 50 m) on backstroke performance and (ii) to analyse the changes in 25 m and 50 m courses backstroke performance across years during the 2000- 2013 period, for both women and men at national (Switzerland) and international (finals of the FINA World Championships) level.